Emotional intelligence and its contribution to language learning - Kotamjani, Sedigheh Shakib; Hussin, Habsah (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
This paper aims to review the significance and importance of emotional intelligence in the process of language teaching and learning. It has been investigated that emotional intelligence plays fundamental role in all aspects of lives; it also has an effective contribution to language teaching and learning, since for learning a language, learners typically need to communicate with people. In domain of language teaching and learning, the concept of emotional intelligence has not broadly identified, applied, or generalized, whereas there are considerable effort s have been made to promote this key concept since two decades ago. To achieve this aim, it is required that researchers and teachers take into account the concept of emotional intelligence and it is required that language teachers promote emotional intelligence in the classroom in order to create efficient and effective learning environment.